Optimization of compressed heat exchanger efficiency by using genetic algorithm - Ghorbani, Mahsa; Ranjbar, S.F. (Zielona Góra: Uniwersytet Zielonogórski)
Due to the application of coil-shaped coils in a compressed gas flow exchanger and water pipe flow in air-conditioner devices, air conditioning and refrigeration systems, both industrial and domestic, need to be optimized to improve exchange capacity of heat exchangers by reducing the pressure drop.
Keywords: heat exchanger; pressure drop; heat capacity; optimization; genetic algorithms